Influence of Rice Husk Biochar and Its Application Methods on Silicon Dynamics and Rice Yield in Sandy-Loam Soil - John S. Olanrewaju; Kuniaki Sato; Sadahiro Yamamoto; Tsugiyuki Masunaga (Applied and Environmental Soil Science)
Rice husk biochar (RHB) is a potential source of available silicon in paddy soil and an ecologically responsive soil amendment for sustainable rice production. The study tested the influence of RHB application methods on rice growth, rice yield, and silicon dynamics in sandy loam soil in a pot experiment. RHB was applied at 5 tons ha−1 as a localized-spot-application (LSA) or top-mixed-application (TMA) with the soil at the upper 7 cm or whole-mixed-application (WMA) within 20 cm of the soil column and at 10 tons ha−1 in the TMA and WMA methods and was compared with a control (CTRL) without biochar. Seedlings of the Koshihikari rice variety were transplanted in each pot, and all treatments were replicated thrice. Compared to the CTRL, the LSA and TMA methods did not influence the mean porewater silicon concentration at the vegetative and reproductive stages. However, the WMA method applied at 5 tons ha−1 increased (p<0.05) the mean porewater silicon concentration by 12.3 and 39.5% at the vegetative and reproductive stages, respectively, while at 10 tons ha−1, the respective increase was by 26.1 and 32.7%. All biochar application methods at the 5 tons ha−1 rate increased the rice grain yield (p<0.05) by 21.2% (LSA), 11.3% (TMA), and 47.2% (WMA) compared to the CTRL. Conversely, at 10 tons ha−1, the yield was reduced by 18% in the TMA method, attributable to the immobilization of nitrogen and adsorption of nutrients to biochar surfaces. Our results proved that the choice of biochar application method and rate of application significantly influenced the dissolution of silicon in the porewater, leading to a higher silicon uptake and consequently a higher grain yield. This study provides valuable insights for agricultural practices aiming to enhance silicon dynamics in paddy soil and sustainable rice yield using RHB.